Unmet care needs of older patients with maxillofacial diseases: A cross-sectional study - Dominika; Ján; Andrea (Magyar Gerontológia, 2025)
Recognizing and addressing unmet care needs is essential for enhancing the quality of healthcare and social support. For patients with maxillofacial diseases who often face complex physical, emotional, and functional challenges, these unmet needs can significantly impact their recovery, well-being, and quality of life.